Rear mechanics is bad mechanics, rethinking sprinting technique and drills (Coaching Track & Field Athletics)
Author has noticed that many sprinters use drills to improve their sprinting technique. Often this includes good old fashioned heel flicks. He is going to ask the question why? He is going to go further and say that heel flicks should be BANNED from your warm up and program.